A Nested Property Right System of the Commons: Perspective of Resource System-Units. Issue 115 (January 2021) - Qi, Yingjun; Li, Wenjun
Highlights: Analyzes the impact of the two individual property rights on the grassland ecological conditions, herders' livelihoods and livestock production. Establishes an analysis framework of grassland property system from the perspective of the resource system and resource units. Highlights the importance of a nested property right system in grassland sustainable management. Provides theoretical perspective for grassland property system and development of CPR theory. Abstract: The common pool resource (CPR) theory has made invaluable contributions to the governance of natural resources in the past decades, but few literatures have specifically paid attention to the different property right arrangements of resource system and resource units, and their relationship. In this paper, we take two types of grassland property right system on the Qinghai-Tibetan Plateau (QTP) in China, one is grassland contract system under that the previous grassland common use was given up and the other is grazing quota system under that the common use is still kept in the community level, as cases to present the different consequences on the ecological conditions, herders' livelihoods and livestock husbandry. Furthermore, from the perspective of property rights of resource system-units, we explore why the two systems resulted in the different consequences. We find that the grazing quota system indicated by the number of livestock each household allowed to raise has more advantages in improving the herders' livelihoods and reducing the livestock production costs, and both systems could alleviate the grazing pressure though the long-term effects of the contract system might be negative on ecological conditions. The main reason why the grazing quota system works better is that this type of individual use rights were clarified based on the resource units so the grassland could be kept common use as an integrated resource system, while the contract system was claimed by physically dividing the resource system by fencing, thus the resource system was fragmented which led to mismatch with the large scope movement needs of livestock grazing. We argue that, theoretically, the grazing quota system is a private property rights embedded in the grassland common property right system, which forms a nested property right regime. Our findings have important implications for both of the CPR theory and practical rangeland management worldwide.